The effect of load on heat production, thermal effects and expenditure of time during implant site preparation – an experimental ex vivo comparison between piezosurgery and conventional drilling. Issue 2 (27th November 2012) - Stelzle, Florian; Frenkel, Carsten; Riemann, Max; Knipfer, Christian; Stockmann, Philipp; Nkenke, Emeka
Abstract Objectives Piezoelectric surgery (PS) is meant to be a gentle osteotomy method. The aim of this study was to compare piezosurgical vs. conventional drilling methods for implant site preparation (ISP) – focusing on load‐dependent thermal effect on hard tissue and the expenditure of ISP time. Materials and methods Three hundred and sixty ISP were performed on ex vivo pig heads using piezosurgery, spiral burs (SB) and trephine burs (TB). The load applied was increased from 0 to 1000 g in 100‐g intervals. Temperature within the bone was measured with a thermocouple, and duration was recorded with a stop watch. Thermal effects were histomorphometrically analysed. Twelve ISPs per technique were performed at the lateral wall of the maxillary sinus. Results PS yields the highest mean temperatures (48.6 ± 3.4°C) and thermal effects (200.7 ± 44.4 μm), both at 900–1000 g. Duration is reduced with a plus of load and significantly longer in either case for PS (P < 0.05). There is a correlation of the applied load with all other examined factors for PS and TB. Temperature and histological effects decrease for SB beyond 500 g. Conclusions PS yields significantly higher temperatures and thermal tissue alterations on load levels higher than 500 g and is significantly slower for ISP compared to SB and TB. For ISP with PS, a maximum load of 400 g should be maintained.